Source or decomposition of soil organic matter: what is more important with increasing forest age in a subalpine setting? - Speckert, Tatjana Carina; Wiesenberg, Guido L. B. (Frontiers in Forests and Global Change, 2023)
Afforestation has been the dominant land-use change in the Swiss Alps during the last decades which has not only the potential to increase soil organic carbon sequestration, but it has also the potential to alter soil organic matter (SOM) dynamics through the vegetation shift and change in organic matter (OM) input into soils. The effects of afforestation on SOM dynamics, however, are still not fully understood as specific sources of OM and modifications of soil processes influencing decomposition and preservation remain largely unknown on alpine to subalpine slopes. Within this study we aimed to identify the potential sources and the decomposition of OM in a subalpine afforestation chronosequence (0-130 years) with Norway spruce (Picea abies L.) on a former pasture by using a multiproxy molecular marker approach. We observed that leaf-derived OM plays an essential role in the pasture areas, while root-derived OM only plays only a minor role in pasture and forest areas. Needlederived OM represents the dominant source of SOM with increasing forest age, while understory shrubs and moss also contribute to the OM input in younger forest stand ages. However, needle litter and buildup of organic layers and subsequently less input of fresh OM from organic horizons to mineral soil can haveresult in the potential to increasedto prime OM decomposition in mineral soils rather than contributing to additional SOM stabilization in mineral soils. This was most pronounced in the oldest forest stand (130-year-old) in the investigated afforestation sequence, particularly in deeper soil horizons (10-45 cm). Thereby, our study provides new insights into SOM dynamics following afforestation, especially with respect to the long-term SOM sequestration potential of afforestation of subalpine pasture soils.